Mechanism of Peak Regulation Auxiliary Electricity Market in the Presence of High-Penetration Renewable Energy and Its Practice in Northwest China - Chen XUE; Jing REN; Xiaowei MA; Wei CUI; Youbo LIU; Xiaodi WANG (Zhongguo dianli)
In the context of power market reform and smart grid development, the source-grid-load flexible interaction, as an inevitable trend of the power system upgrading, can perform as a promising method to address the peak-regulation resources shortage issue in Northwest China. This paper firstly summarizes the key technologies and their practical applications such as the market mechanism and trading varieties of auxiliary service market in the presence of high-penetration renewable energy. Based on the current peak-regulation auxiliary service market in the Northwest China region, a coordinated source-grid-load flexible interaction framework is proposed according to the load characteristics of the northwest grid and the accommodation demand of renewable energy. It is expected to stimulate various market entities to participate in peak-regulation service, so as to maximally consume renewable energy while ensuring the safe and economic operation of the power grid.